Censurae Librorum - Bibik, Barbara (Polskie Towarzystwo Filologiczne, 2018)
David Stuttard (ed.), Looking at Antigone, London: Bloomsbury, 2018, 247 pp., ISBN 978-1-3500-1711-5, £85.00
Keywords: censurae liborum